Association of B7-H4 gene polymorphisms in urothelial bladder cancer - Di̇nçel, Deni̇z; Şamli, Hale; Balci, Faruk; Sağlican, Yeşim; İnce, Ümit; Şahi̇n, Ahmet; Samli, Murat; Ozgoz, Asuman (The Scientific and Technological Research Council of Turkey (TUBITAK-ULAKBIM) - DIGITAL COMMONS JOURNALS, 2017)
We aimed to study polymorphisms of the B7-H4 gene in order to evaluate a possible association in urothelial carcinoma, as it is highly expressed in cancer tissues.In this study B7-H4 gene rs10754339, rs10801935, and rs3738414 SNPs were studied by PCR-RFLP method in paraffin-embedded tumor specimens from 62 urothelial carcinoma patients and in a control group including 30 patients without bladder cancer.We detected that the rs10754339 polymorphism was more frequent in the cancer patients when compared with the control group (P < 0.05). Only the rs3738414 polymorphism showed a statistically significant difference in frequency between pathologic diagnostic groups.The rs10754339 AA genotype distribution was found to have a higher frequency whereas the rs3738414 AG genotype distribution was lower in the bladder cancer group (P < 0.05). None of the genotype distributions showed a significant difference from the control group for the rs10801935 polymorphism. We conclude that B7-H4 has the potential to be a useful prognostic marker in urothelial carcinoma.
Keywords: Male; Bladder cancer; Middle Aged; V-Set Domain-Containing T-Cell Activation Inhibitor 1; Real-Time Polymerase Chain Reaction; Polymorphism, Single Nucleotide; polymorphism; Gene Frequency; Urinary Bladder Neoplasms; Predictive Value of Tests; Biomarkers, Tumor; Humans; B7-H4 gene; Female; Urothelium; Genetic Association Studies; Aged; 3. Good health